Skills Mismatch in Small-sized Enterprises in Malaysia - Anuar, Abdul Rahim; Mansor, Wan Nurmahfuzah Jannah Wan; Din, Badariah Haji (International Journal of Economics and Financial Issues, 2016)
The purpose of this study was to determine the skill mismatch faced by small-sized enterprises (SSEs) in Malaysia. The respondents were 242 human resource managers from selected SSEs in Malaysia. All variables showed a positive relationship towards skill mismatch among employees. The data were analyzed by using multiple statistical procedures, namely mean point value and correlation analysis. The result of the study showed that numerous SSEs faced issues of lack of skills in their workers. They acknowledged the existence of skill mismatch in the form of skill gap, horizontal mismatch, and over-education among their workers. Thus, they need to change the recruitment strategy and focus on skill training programs that could help workers to perform better and improve their productivity performance. Keywords: Small-sized enterprises, Skill mismatch, Productivity JEL Classifications: J00, J4